Association between pet ownership and physical function at discharge in hospitalized older adults: A retrospective observational study - Yo Ishihara; Kiyomitsu Fukaguchi; Hiroshi Koyama (PLoS ONE, 2025)
Objectives Hospitalization can lead to a loss of physical function among older adults. While pet ownership has been reported to have beneficial effects on physical function, its impact on hospitalized patients remains unclear. We examined the association between pet ownership upon admission and physical function during hospitalization. Methods This single-center, retrospective, observational study was conducted between April 2013 and April 2023. Patients aged ≥65 years who were hospitalized for the first time due to pneumonia at our facility were included. Cases were identified through medical record searches using the keywords “pet”, “dog”, “cat”, “ownership”, and “keeping”. Patients with unclear pet ownership status in the medical records were excluded from the analysis. Patients were classified into two groups: Pet Owners (PO) and Non-Pet Owners (NPO) upon admission. The Barthel index (BI) gain (the difference between admission and discharge BI scores) and BI efficiency (BI gain divided by hospital stay) were compared. Logistic regression was performed for patients with a BI gain >0 and discharge BI scores >85, indicating independence without functional decline, after adjusting for covariates. Results A total of 248 patients were initially screened, we finally included 172 patients (69.4%) in the PO group and 46 patients (18.5%) in the NPO group. The median BI gain was 10 (0–30) and 2.5 (0.0–26.3) in the PO and NPO groups (p = 0.24), respectively. The median BI efficiency was 0.48 (0.00–1.87) and 0.16 (0.00–1.27) in the PO and NPO groups (p = 0.062), respectively. Current pet ownership was not associated with independence without functional decline, with an adjusted odds ratio of 0.68 (95% confidence interval, 0.15–3.94; p = 0.63). Conclusions This study found no association between current pet ownership and the maintenance of physical function in hospitalized older adults.